METHOD OF OPERATIVE TREATMENT OF POSTNECROTIC CYSTS OF THE PANCREAS - V. L. Poluektov; S. V. Morozov; V. T. Dolgikh; A. I. Lobakov; A. B. Reis (Вестник хирургии имени И.И. Грекова, 2016)
An analysis of treatment results was made in 26 patients with postnecrotic cysts of different degree of maturity. The laparotomy with trans-gastral cystogastrostomy on the external drainage were performed on 11 patients. A new modified operation underwent 15 patients. This operation was transgastric cystogastrostomy on the external drainage from mini-access, which was developed in 2011. The laparotomy of 4-5 cm was made in pseudocyst projection of the pancreas using a standard set of tools «mini-assistant». Postoperative period have passed without complications in all the patients. The drainage was removed on 30-40 days of postoperative period. The terms of hospital stay reduced from (14,4±0,9) bed/ days to (10,8±0,5) bed/days due to application of proposed method of treatment.